Development And Evaluation Of Novel Aqueous Neem Leaf Extract: A Potent Contraceptive Agent (Journal of Pharmaceutical Negative Results, 2022)
In the midst of the global epidemics of both unwanted pregnancies and sexually transmitted infections (STIs), possibilities that provide protection with minimal side effects are ideal. Therefore demand is increasing for vaginal contraceptives which protect from infection too. The spermicidal activity was determined using a modified method of Sander and Cramer. The extract was mixed with sperm suspension containing sperm. The mixture was mounted on the stage of Polarized microscope for 20 s at 100x (oil immersion) and observed for motile sperm. The spermicidal activity of novel aqueous neem extract on rat spermatozoa was same as in case of human spermatozoa. . The MEC of NANE was found to be 2.5 mg/ml and 5 mg/ml in rat and human spermatozoa respectively. The present study describes the simple, one step, novel method of extraction and evaluation of in-vitro spermicidal activity in rat spermatozoa and in-vivo contraceptive efficacy in female wistar rat. It may be concluded that prolonged and controllable drug delivery of neem constituents from mucoadhesive gel with various loading doses, is achievable and delivered dose in controlled manner for fertility control.